Staged angioplasty using a full-length balloon catheter to achieve maturation of arteriovenous fistulas - Chung Won Lee; Chang Ho Jeon; Sung Woon Chung; Chung Won Lee; Up Huh; Jongwon Kim; Hyuncheol Jeong (Diagnostic and Interventional Radiology)
PURPOSE: To evaluate the efficacy of staged full-length balloon-assisted maturation (BAM) for the maturation of arteriovenous fistulas (AVFs) on entire segmental veins, including stenosis, causing primary AVF failure. METHODS: This study included patients who underwent AVF surgery using an autogenous vein between February 2020 and June 2021 and received staged angioplasty with a full-length balloon catheter. To minimize balloon overlap and the risk of barotrauma to the immature vein, serial-staged upsizing balloon angioplasty with a long balloon catheter covering the entire vein segment was employed approximately 2 weeks apart. RESULTS: Twenty-three patients (mean age, 69.50 years; mean follow-up, 620.62 days) with average diameters of the radial artery and cephalic vein at 2.14 ± 0.5 mm and 2.43 ± 0.5 mm, respectively, were enrolled. In the first procedure, the average AVF diameter and flow were 4.03 ± 0.57 mm and 438.08 ± 220.95 mL/min, respectively, with juxta-anastomotic stenosis (JAS) present in 61.5% of cases. After staged full-length BAM, the average fistula diameter and flow improved to 5.95 ± 0.86 mm and 717.52 ± 305.95 mL/min, respectively. Maturation was achieved in 87% of the cases. No hematomas or ruptures occurred around the arterialized veins. Despite successful maturation and cannulation, 65.2% of the patients required additional percutaneous transluminal angioplasty (PTA) during the follow-up period. The necessity for PTA was determined by the presence of JAS prior to the first staged full-length BAM, with an odds ratio of 11.74 (95% confidence interval: 1.31–104.96, P = 0.03). CONCLUSION: Staged full-length BAM can be safely used in patients with small veins requiring further maturation. Most patients achieved successful cannulation following maturation without post-procedural complications. CLINICAL SIGNIFICANCE: Staged full-length BAM is a safe and effective method for enhancing maturation in patients with underdeveloped small veins.